Korelasi antara Kesehatan Mental dan Kecemasan dengan Prestasi Atlet Tennis di Klub SPTC Kota Tegal - Fitri, Adinda Syelvia; Sungkowo; Soedjatmiko; Ulinnuha, Rizam Ahada Nur (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The study aims to identify the relationship between mental health and anxiety with the achievement of tennis athletes at the SPTC club in Tegal City. The research was based on the background that the importance of mental health and anxiety as psychological factors that can affect athlete performance in achieving optimal performance. The research approach, applying descriptive quantitative by involving 9 outstanding athletes who were selected selectively through purposive sampling techniques. Research instruments include mental health questionnaires, anxiety, and athlete achievement score data. The results of the analysis show that there is no significant relationship between mental health and athlete achievement, indicated by a significance value of 0,086 wich exceeds the 0,05 threshold. Conversely, there is a significant relationship between anxiety and athlete performance with a significance value of 0,007 which below 0,05. Simultaneously, mental health and anxiety are jointly related to athlete performance, although individually only anxiety has a significant relationship to athlete performance. These findings emphasize the need for special attention to psychological aspects, especially aspect of anxiety, as an effort to improve athlete performance.